Modelling and analysis for a cylindrical net-shell deployable mechanism. Issue 15 (November 2019) - Lin, Fei; Chen, Chuanzhi; Chen, Jinbao; Chen, Meng
Existing cylindrical deployable structures have poor controllability of deployment or weak bearing capacity. In order to satisfy the application needs of cylindrical deployable structures in the space industry, a cylindrical net-shell deployable mechanism is established in this article. The proposed cylindrical net-shell deployable mechanism has a regular cuboid shape in the folded state and a truss structure in the deployed state, and it can fit cylindrical surface, parabolic cylindrical surface, sine cylindrical surface and so on. Furthermore, based on reciprocal screw theory and screw synthesis theory, the mobility of cylindrical net-shell deployable mechanism in the whole motion cycle is analysed by the proposed equivalent model method. Results show that the cylindrical net-shell deployable mechanism is a single-degree-of-freedom mechanism. Moreover, a prototype is manufactured, and its motion performance is tested. The experiment shows that the cylindrical net-shell deployable mechanism has a smooth motion performance, and the mobility analysis method for complex coupled mechanism in this study is valid. This study has a certain significance in expanding the application field of cylindrical shell structure.